ISLAMIC GATHERING AS A MEDIA INCREASING THE SPIRITUAL INTELLIGENCE OF STUDENTS AT INFORMATICS VOCATIONAL SCHOOL IN THE ERA OF COVID-19 - Eri Murniasih; Wasehudin Wasehudin (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
The purpose of this study is to see how the implementation of the Islamic Gathering program at the Informatics Vocational School in Serang City during the Covid-19 pandemic influenced students' spiritual intelligence. The descriptive qualitative method was used in this study. The data were gathered through interviews and observations. Oral interviews were performed with the principal, three teachers participating in the implementation of Islamic gathering events, specifically teachers of Islamic Religious Education subject, and 12 students from classes XI and XII. Observations were also conducted on the activities and students at the Islamic Gathering. The study's findings revealed that the Islamic Gathering program is an activity that combines religious studies with religious routines from noon to noon, and that during the COVID-19 pandemic, this activity was carried out both online and offline, with the goal of increasing students' spiritual intelligence as evidenced by changes in their attitudes, such as the ability to live more valuable lives, and changing students' perspectives toward religion.